A Hybridized Monitor Receiver for Low Band FM. (1981) - Brown, Alan T.
Abstract : Certain aspects of the design and implementation of a hybridized monitor receiver are discussed. The receiver is realized in thick film technology. Screened capacitors as well as an adjustable inter-digitated thin film capacitor are employed in the design. Fine tuning of the crystal controlled local oscillator is achieved by abrasive trimming of monolithic chip capacitors. Modularization of the receiver lends itself towards simplified circuit construction and alignment.